Magnetization mechanisms for non-destructive evaluation of low-carbon steels subject to early-stage low-temperature thermal oxidation - Mongshi, Anita; Tene Deffo, Yves Armand; Mary, Nicolas; Tsafack, Pierre; Mogniotte, Jean-François; Ducharne, Benjamin (Journal of magnetism and magnetic materials, 2024)
In this work, an investigation is done to identify the magnetic non-destructive testing techniques and their related magnetization mechanisms and, eventually, the associated indicators that present the most distinguishable response to changes in steel properties due to the onset and evolution of starting corrosion by thermal oxidation at low temperatures. This is found by measuring magnetic responses of Magnetic Hysteresis Cycle (MHC), Magnetic Barkhausen Noise (MBN), and Magnetic Incremental Permeability (MIP) at the early stage of corrosion. Herein, the magnetization mechanism identified by the Domain Wall Bulging (DWB) effect and represented by the indicator Δ|Z|MIP from the MIP response is ranked the most sensitive indicator by Pearson’s linear correlation coefficient (LCC). It is immediately followed by the Domain Wall’s Irreversible Motions (DWIM) represented by the MBN coercivity indicator. Both mechanisms are associated with the structure and kinetic of the magnetic domains, respectively, under low and medium magnetic excitations. The low-temperature thermal oxidation process set out the constructive effect of the oxide layer in the strain relief effect on the overall magnetic response of the corroded specimen. Discussions and conclusions are provided, as well as perspectives regarding the applicability of magnetic non-destructive testing techniques.